Impact of muscle mass on the prognosis of liver transplantation for infants with biliary atresia - Lledín, María D.; Parrón-Pajares, Manuel; Morais, Ana; Hernández-Oliveros, Francisco; Botella-Carretero, Jose I.; Hierro, Loreto (Frontiers in Pediatrics, 2023)
Background: Sarcopenia in adult cirrhotic patients is associated with increased morbidity and mortality whereas in children it is still being studied. Anthropometric variables in cirrhotic children are not reliable for assessing muscle mass as they may be altered by ascites, edema, and organomegaly. Measuring the area of the psoas showed good correlation with muscle mass in adults. We aimed to study in cirrhotic infants undergoing liver transplantation the association of the psoas area with liver transplant prognosis as well as with several analytical and anthropometric parameters used to evaluate nutritional status. Methods: Retrospective cohort of 29 infants with cirrhosis due to biliary atresia who underwent abdominal CT scan as a pre-transplant study. We measured the psoas muscle index (PMI) at L4-L5 since it best correlates with muscle mass in pediatric patients. As there are no validated cut-off points to define sarcopenia in children under one year of age, PMI was recorded as a continuous variable and correlated with different prognostic, clinical, and analytical variables. The SPSS 17.0 package was used for statistical analysis and a P<0.05 was considered significant. Results: 29 infants (10 boys, 19 girls) were studied. 62% were Caucasian and the rest were South American. The mean age at CT scan was 8.5 months (range 3-15 months). There was a negative correlation between PMI and days of admission prior to liver transplant, previous infections, and bone fractures. Among the analytical parameters, cholinesterase, albumin, and prealbumin correlated positively with PMI (P<0.05). No relationship was observed with anthropometric parameters: weight, height, BMI, brachial perimeter, or bioimpedance. During surgery, patients with lower PMI had a greater need for plasma transfusion, and in the immediate postoperative period, there was a longer stay in intensive care, more days of mechanical ventilation, and more days of hospital admission (P<0.05). On the contrary, no relationship was found with other complications: bleeding, re-interventions, biliary leaks, rejection, thrombosis, re-transplantation, or infections. Conclusions: The decrease in muscle mass is associated with increased morbidity in infants with biliary atresia undergoing liver transplantation. Muscle mass in these patients cannot be adequately assessed with anthropometric measurements commonly used in the clinic.